The Auditory Dimension of Power in the Urban Areas of the Kingdom of Castile between the Late Middle Ages and Early Modernity - Coronado Schwindt, Gisela (Huarte de San Juan. Geografía e Historia, 2023)
Both present and past cities are producers of a multiplicity of sounds and noises that account for their specificities as urban organizations. In this sense, it can be seen that sound events were vital elements of the Castilian urban system since they configured the way in which the subjects travelled through time, space and the social sphere of the city. Consequently, the objective of this work will be to identify and analyze the royal and council auditory realm in certain Castilian urban spaces during the 15th and 16th centuries, through royal and municipal documentation, by identifying the aural marks of the oral practices of the authorities in the municipal and judicial spheres. This will allow us to reflect on the importance of the act of listening in certain contexts and thereby conceive an auditory epistemology of power in the citizen framework. Key words: City – Castile – sounds – listening – power